2002
DOI: 10.1074/jbc.m112217200
|View full text |Cite
|
Sign up to set email alerts
|

Lysolipids Do Not Inhibit Influenza Virus Fusion by Interaction with Hemagglutinin

Abstract: The interaction of a spin-labeled lysophosphatidylcholine analog with intact and bromelain-treated influenza viruses as well as with the bromelain-solubilized hemagglutinin ectodomain has been studied. The inhibition of fusion of influenza viruses with erythrocytes by the lysophosphatidylcholine analog was similar to that observed for non-labeled lysophosphatidylcholine. Only a weak interaction of the lysophosphatidylcholine analog with the hemagglutinin ectodomain was observed even upon triggering the conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…It is interesting that liposomes containing TPE (phospholipid inducing negative curvature) displayed relatively high hemifusion and fusion values, whereas liposomes containing LPC (phospholipid inducing positive curvature) were the ones that elicited the lowest values. This inhibitory effect produced by inverted-coneshaped phospholipids has been previously observed in some viral and nonviral fusion systems (67)(68)(69)(70). This effect could be due to the fact that E2 FP , located at the bilayer interface and interacting with the phospholipid headgroups, could be capable of changing the polymorphic phase behavior of the membrane bilayer, since it was able to inhibit the presence of hexagonal phases but induce the presence of other lamellar phases (isotropic 31 P-NMR signal, but lamellar SAXD diffraction pattern).…”
Section: Discussionsupporting
confidence: 63%
“…It is interesting that liposomes containing TPE (phospholipid inducing negative curvature) displayed relatively high hemifusion and fusion values, whereas liposomes containing LPC (phospholipid inducing positive curvature) were the ones that elicited the lowest values. This inhibitory effect produced by inverted-coneshaped phospholipids has been previously observed in some viral and nonviral fusion systems (67)(68)(69)(70). This effect could be due to the fact that E2 FP , located at the bilayer interface and interacting with the phospholipid headgroups, could be capable of changing the polymorphic phase behavior of the membrane bilayer, since it was able to inhibit the presence of hexagonal phases but induce the presence of other lamellar phases (isotropic 31 P-NMR signal, but lamellar SAXD diffraction pattern).…”
Section: Discussionsupporting
confidence: 63%
“…Consistent with the requirement for strong bending of the outer membrane leaflets for stalk formation, our data have shown that incorporation of invertedcone-shaped lipids (positive curvature) such as LPC in this leaflet of the target membrane had a strong inhibitory effect on fusion, whereas it was slightly enhanced when cone-shaped lipids (negative curvature) were used. Similar inhibitory effects of inverted-cone-shaped lipids that could be related to membrane curvature effects have been observed in a number of viral and nonviral fusion systems, including influenza virus (3,9), baculovirus (7), human immunodeficiency virus (33), rabies virus (15), cortical granule exocytosis (50), and microsome fusion (10).…”
Section: Discussionmentioning
confidence: 95%
“…To study both processes, a significant number of different experimental models have been developed that are primarily based on viral binding studies to glycophorin or ganglioside containing liposomes. , In these models the fusion of two spherical objects, the virus and the liposome, is monitored but in situ target tissues are nonspherical and are formed by planar cellular monolayers of ganglioside exposing cells. However, there is also a significant number of studies that show that the lipid curvature of the liposome is a parameter that influences fusion efficiency of the influenza and other viruses. , Here we report a new experimental model that is based on the viral binding to planar, mica supported membranes containing gangliosides. The observations made on this system therefore does not depend on the intrinsic curvature of target membranes.…”
Section: Discussionmentioning
confidence: 99%